Chp1 is a dedicated chaperone at the ribosome that safeguards eEF1A biogenesis - Minoia, Melania; Quintana-Cordero, Jany; Jetzinger, Katharina; Kotan, Ilgin; Turnbull, Kathryn Jane; Ciccarelli, Michela; Masser, Anna E.; Liebers, Dorina; Gouarin, Eloïse; Czech, Marius; Hauryliuk, Vasili; Bukau, Bernd; et al. (Nature Communications, 2024)
Cotranslational protein folding depends on general chaperones that engage highly diverse nascent chains at the ribosomes. Here we discover a dedicated ribosome-associated chaperone, Chp1, that rewires the cotranslational folding machinery to assist in the challenging biogenesis of abundantly expressed eukaryotic translation elongation factor 1A (eEF1A). Our results indicate that during eEF1A synthesis, Chp1 is recruited to the ribosome with the help of the nascent polypeptide-associated complex (NAC), where it safeguards eEF1A biogenesis. Aberrant eEF1A production in the absence of Chp1 triggers instant proteolysis, widespread protein aggregation, activation of Hsf1 stress transcription and compromises cellular fitness. The expression of pathogenic eEF1A2 variants linked to epileptic-dyskinetic encephalopathy is protected by Chp1. Thus, eEF1A is a difficult-to-fold protein that necessitates a biogenesis pathway starting with dedicated folding factor Chp1 at the ribosome to protect the eukaryotic cell from proteostasis collapse.